Identification of Alnus acuminata ectomycorrhizae from Argentinean alder stands using anatomical characterization and ITS-sequence analysis - Pritsch, Karin (2010)
The objective of this study was to describe the morphological and anatomical features of five unidentified ectomycorrhizal types of Alnus acuminata and to complement their identification using ITS-DNA sequence analysis. The combined approach of morphotyping and sequence analysis based on ITS sequence comparison with sequences contained in GenBank and the UNITE database allowed us to assign three of the five field- collected ectomycorrhiza morphotypes to the tomentella-thelephora lineage that matched closely to European and North American species. The sequencing results within Tomentella point towards alder specific lineages within T. sublilacina, T. ellisii, and T. stuposa. The two other EcM morphotypes matched with Lactarius omphaliiformis and a Russula sp. Better focused, concomitant fruit-body surveys are needed for accurate identification of South American ectomycorrhizal fungi, because of the evidence of cryptic speciation events in both agaricoid and resupinate mycobionts.